PUBLIC RESPONSE TO THE ISSUES OF POLITICAL DYNASTIES IN 2024 INDONESIAN ELECTION: ANALYSIS OF SPEECH ACTS - Mahmud, Murni; Burhamzah, Muftihaturrahmah; Awaliyah, Nurul Husnul (Faculty of Languages and Literature, Universitas Negeri Makassar, 2025)
An increasing number of academics, policy makers, and democracy activists are concerned about the rise of political dynasties in democratic societies, especially in cases of democratic consolidation. This dynastic phenomenon has received serious attention in the Indonesian political context. Especially in the last few decades, political dynasties have integrated themselves into the electoral process in Indonesia. In advance of the 2024 election, there were quite a few happenings centered around the topic of political dynasties in Indonesia, particularly during the election this year and under President Jokowi's governance. This research aims to examine how people responses about issue political dynasties that occurred in the 2024 Indonesian general election. This study analyzed public opinion towards political dynasties in elections, including the level of concern, understanding and attitudes towards this practice, using survey methods and qualitative data analysis. Discourse analysis is used in this research as part of a qualitative descriptive methodology. The data was collected by reading the comments of the people regarding the issue of political dynasties raised by President Jokowi in the 2024 election on various social media platforms, including YouTube, Instagram and TikTok, and Twitter. This research examines the discourse surrounding political dynasties on social media during Jokowi's presidency in Indonesia. Through analysis of various quotes, it identifies assertive, expressive, and directive speech acts used to convey opinions on political dynasties. Drawing on John Searle's speech act theory, the study highlights the complexity of social media communication and its role in shaping public opinion. Criticism of political dynasties reflects concerns about democracy, while some support them as expressions of widespread endorsement. The research emphasizes the importance of understanding the nuanced meanings behind social media discourse and the need for open dialogue to promote democratic principles.